PERAN PEMERINTAH KABUPATEN INDRAGIRI HILIR DALAM MENDORONG EKSPOR KELAPA KE MALAYSIA TAHUN 2020–2025: ANALISIS PARADIPLOMASI EKONOMI DAERAH - Mohd. Ilham; Erif Wicaksana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This study examines the role of the Indragiri Hilir Regency Government in promoting coconut exports to Malaysia during the 2020–2025 period through the perspective of economic paradiplomacy. Indragiri Hilir is recognized as the largest coconut-producing region in Indonesia, making coconut a strategic commodity that significantly contributes to regional economic development and community livelihoods. This research employs a qualitative method with a case study approach. Data were collected through interviews, documentation, and the review of relevant secondary sources, and were analyzed using the interactive data analysis model developed by Miles and Huberman. The findings reveal that the Indragiri Hilir Regency Government plays a strategic role as a facilitator, regulator, and promoter in supporting coconut export activities to Malaysia. These roles are reflected in the provision of assistance to farmers and business actors, facilitation of export administration and licensing processes, development of trade-supporting infrastructure, promotion of regional flagship commodities, and efforts to encourage coconut product downstreaming. Malaysia remains the primary export destination due to its geographical proximity, high industrial demand for coconut-based raw materials, and long-standing trade relations. However, export development continues to face several challenges, including inadequate logistics infrastructure, commodity price fluctuations, limited value-added processing, and dependence on raw commodity exports. This study concludes that the economic paradiplomacy undertaken by the Indragiri Hilir Regency Government has contributed to expanding international market access, enhancing the competitiveness of coconut commodities, and strengthening regional economic development based on local resource advantages. Keywords: Paradiplomacy, Local Government, Coconut Export, Malaysia, Indragiri Hilir.